2015
DOI: 10.1038/modpathol.2015.97
|View full text |Cite
|
Sign up to set email alerts
|

Periductal stromal collagen topology of pancreatic ductal adenocarcinoma differs from that of normal and chronic pancreatitis

Abstract: Pancreatic ductal adenocarcinoma continues to be one of the most difficult diseases to manage with one of the highest cancer mortality rates. This is due to several factors including nonspecific symptomatology and subsequent diagnosis at an advanced stage, aggressive metastatic behavior that is incompletely understood, and limited response to current therapeutic regimens. As in other cancers, there is great interest in studying the role of the tumor microenvironment in pancreatic ductal adenocarcinoma and whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
117
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(128 citation statements)
references
References 61 publications
11
117
0
Order By: Relevance
“…31 In addition, in the context of the tumor microenvironment, an extreme collagen-rich stromal response is a hallmark of pancreatic cancer and can account for up to 90% of the tumor mass. 32 Furthermore, characteristic changes in collagen alignment have been documented, 12 and other stromal cues have been correlated to patient prognosis. 33 Consistent with previous SHG trends, 12 we found that key collagen properties, such as alignment, were computed to be higher in pancreatic cancer tissues compared with normal adjacent tissues using picrosirius red stain with standard polarization microscopy (PSR-POL).…”
Section: Research-article2016mentioning
confidence: 99%
See 3 more Smart Citations
“…31 In addition, in the context of the tumor microenvironment, an extreme collagen-rich stromal response is a hallmark of pancreatic cancer and can account for up to 90% of the tumor mass. 32 Furthermore, characteristic changes in collagen alignment have been documented, 12 and other stromal cues have been correlated to patient prognosis. 33 Consistent with previous SHG trends, 12 we found that key collagen properties, such as alignment, were computed to be higher in pancreatic cancer tissues compared with normal adjacent tissues using picrosirius red stain with standard polarization microscopy (PSR-POL).…”
Section: Research-article2016mentioning
confidence: 99%
“…32 Furthermore, characteristic changes in collagen alignment have been documented, 12 and other stromal cues have been correlated to patient prognosis. 33 Consistent with previous SHG trends, 12 we found that key collagen properties, such as alignment, were computed to be higher in pancreatic cancer tissues compared with normal adjacent tissues using picrosirius red stain with standard polarization microscopy (PSR-POL). Interestingly, all of the collagen measurements that we considered were computed to be significantly higher in the PSR-POL images relative to SHG images.…”
Section: Research-article2016mentioning
confidence: 99%
See 2 more Smart Citations
“…This also involves integrin mechanosignalling that amplifies epidermal growth factor receptor (EGFR) dependent PI3 kinase (PI3K) signalling [16]. Furthermore, the periductal collagen in PDAC exhibits architectural and structural differences in terms of linearization, alignment, and thickness, which can serve as an independent prognostic factor but might also facilitate cancer invasion through topographical contact guidance [27,28]. New imaging modalities such as second harmonic generation (SHG) imaging and elastography enable visualisation of cell-matrix interactions in 3D environments (in vitro) [29] and assessment of mechanical properties of tissues (in vivo) [30] and will help advance our understanding how structural, topographical, and mechanical changes of the microenviron ment can impact cancer cell behaviour.…”
Section: Mechanical Forces Play Key Role In Pdacmentioning
confidence: 99%